Analysis of Drying Process of Water-Based Architectural Paints - Barcelos, Gustavo Feliciano de Jesus; Souza, Paula Duarte de Carvalho; Cotting, Fernando (Orbital: The Electronic Journal of Chemistry, 2021)
Due to its low toxicity and because they are environmentally friendly, water-based paints are the most employed in the world, mainly to coat buildings. In these systems, the water evaporation process is important to determine the final paint quality and should be carefully evaluated. This work evaluated the suitability of Crank’s model, solution of the Fick’s second law, to experimental drying data of water-based architectural paints to better understand this process. Therefore, the data were adjusted to the linearized and original model and the number of terms used in its approximation was varied. For each model, the diffusion coefficient of the water in the coating material and the coefficient of determination were calculated. The results showed that the use of the linearized model is not adequate to determine the diffusion coefficient, but the nonlinear adjustment of the original model can adjust the data for some paints. These results also suggest the addition of terms to the sum of the model to improve its quality in the initial stages of drying. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1508